Enhancing Monomeric Sugar Production from Coconut Husk by FeCl3-assisted Hydrothermal Pretreatment and Enzymatic Hydrolysis - Wijaya, Candra; Sangadji, Ningsi Lick; Muharja, Maktum; Widjaja, Tri; Riadi, Lieke; Widjaja, Arief (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
Coconut husk (CCH), an abundant agricultural byproduct of the coconut processing industry, holds significant potential as a renewable feedstock for monomeric sugar production. However, efficient fractionation remains a challenge due to its recalcitrant lignocellulosic structure. This study investigates FeCl₃-assisted hydrothermal pretreatment (HTP) as a selective and scalable approach to enhance enzymatic hydrolysis efficiency and sugar recovery. The effects of FeCl₃ concentrations, temperatures, and unified of pretreatment conditions as combined hydrolysis factor (CHF) on biomass fractionation, modeling xylan dissolution, and monomeric sugar production were evaluated. Results indicate that 0.06 M FeCl₃ at 150 °C achieved the highest total monomeric sugar concentration of 7.364 g/L, an 11-fold increase compared to the non-catalyzed control (0.667 g/L) during HTP. This condition also facilitated 81.2% hemicellulose removal while minimizing cellulose and lignin degradation, thereby improving enzymatic digestibility. Furthermore, xylan hydrolysis also successfully developed with high correlation with unified CHF parameter. FeCl₃-assisted HTP CCH coupled with enzymatic hydrolysis further enhanced overall sugar recovery, with a total monomeric sugar yield of 18.4 g per 100 g raw CCH, representing a 4.4-fold increase compared to hydrothermally pretreated CCH without FeCl₃. These findings highlight FeCl₃-assisted HTP as a promising, cost-effective strategy for biomass fractionation, supporting its integration into lignocellulosic biorefineries for bio-based product development. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).